A century of economic growth in Latin America - Astorga, P (University of Oxford, 2009)
This paper makes a contribution to the study of economic growth in developing countries by analysing the six largest Latin American Economies over 105 years within a two-equation framework. Confirming previous findings, physical and human capital prove to be key determinants of GDP per capita growth. However, a more controversial result is an overall negative conditional correlation between trade openness and GDP per head growth - though openness has a positive link via investment. The evidence also shows that macroeconomic instability has been a drag on long-term growth in the region.